Pillar[6]arene-modified gold nanoparticles grafted on cellulose nanocrystals for the electrochemical detection of bisphenol A. (22nd July 2021) - Tan, Xiaoping; Yang, Hongxing; Ran, Xin; Li, Zhi; Zhang, Lianpeng; Gao, Wei; Zhou, Xiaojian; Du, Guanben; Yang, Long
Abstract : The as-prepared CNCs@CP6-AuNP nanohybrid and its application in sensing BPA. Abstract : In this study, a macrocyclic cationic pillar[6]arene (CP6)-modified gold nanoparticle (CP6-AuNP)-functionalized cellulose nanocrystal (CNC) nanohybrid is prepared. The obtained CNC@CP6-AuNP nanohybrid exhibits high electrocatalytic activity and excellent selective molecular recognition capability towards the electrochemical determination of bisphenol A (BPA). The electrode, operated at a working potential of 0.3 to 0.9 V, works in the concentration range of 0.05–100 and 100–500 μM BPA and has a 12 nM detection limit. The host–guest interactions are studied via fluorescence titration experiments, indicating more affinity and a high binding constant ( K a ) of 4.29 × 10 4 M −1 by electrostatic interactions and hydrophobic interactions between CP6 and BPA. The electrochemical sensing has also been used to detect BPA in tap water and milk samples with satisfactory results. Finally, this study can provide a novel method for the design of a macrocycle host-modified metal nanoparticle-functionalized hybrid material for catalysis, sensing, materials science and other fields.